THE ROLE OF FINTECH IN THE FINANCIAL MARKET DEVELOPMENT IN UKRAINE - Fedyshyn , M. P.; Zhurko , R. V.; Lobko , O. M. (The actual problems of regional economy development, 2024)
In the article, the main stages of the historical development of the FinTech industry in the global financial markets are investigated, namely: stage 1 (1866–1967) – emergence of telegraphic lines of communication and information transmission; stage 2 (1967–2009) – introduction of the main payment instrument – a plastic payment card – into mass circulation; stage 3 (2009 р.–2024) – emergence of financial and outsourcing companies providing FinTech services. According to the defined stages, the author groups and forms the FinTech concepts of foreign and domestic leading scientists in the field of digital technologies of the financial market and provides the author’s definition of this concept. Three key models of the FinTech implementation in the global economy are presented, such as the US-China BigTech model, the European model (Startup FinTech) and the Ukrainian model or Traditional - FinTech. The identifies the models of the FinTech implementation that emerged after 2020-2022 and consist of the following elements: providers of financial products, “digital killers” of FinTech services, and digital personal managers. In the article, the criteria and principles of the FinTech innovation in the financial market of the state are presented, which include the following components: the principle of openness of financial services, the principle of subjectivity of FinTech services, the principle of technological effectiveness, which forms the concept of the FinTech innovations, and the principle of focus, based on which the development level of the FinTech trends in Ukraine are determined. The main participants of the FinTech financial market of Ukraine are identified, including consumers of the financial services, business structures, participants of traditional markets and companies of financial services. The article presents a number of functions performed by FinTech in the financial market, the main ones being the use of cloud technologies and access to financial data, reduction of the time to market for a new product and the ability to combine consumer data and available services. The article analyses the strengths and weaknesses of the Ukrainian FinTech market. The terms and stages of the development of the FinTech Development Strategy in Ukraine are studied. The level and technologies of the FinTech use in the financial markets of the world’s leading countries and their ecosystem of financial and technological clusters are investigated.